Scientometric Analysis of Autism Research Output during 2007-2011 - Jeyshankar, R.; Vellaichamy, A. (Journal of Information and Knowledge, 2016)
In the present study, we attempt to analyse 13079 global literature on Autism, indexed in Scopus database during 2007-11. Totally 70 countries contributed to the literature, majority of the papers coming from USA (49.24%), followed by United Kingdom (15.61%), Germany (4.93%) etc. The study analysed that Indian scientists together have published 134 papers on Autism research during 2007-11. India ranks 17th among the other countries in Autism research with a global publications share of 1.01% during 2007-11. In depth, this study analysed that majority of the publications are published in the form of articles (64.76%) and majority (79%) of the scientists preferred to publish their research papers in joint authorship. The study also analysed that majority of the autism research appeared in Journal of Autism and Developmental Disorders (7.19%) followed by Research in Autism Spectrum Disorders (2.34%) and Autism (1.87%). "Nature" has highest number of citations (822) followed by "Science" (717) and "Annals of the New York Academy of Science" (628).